2010
DOI: 10.1111/j.1539-6924.2010.01503.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Risk Assessment Modeling for Nonhomogeneous Urban Road Tunnels

Abstract: Urban road tunnels provide an increasingly cost-effective engineering solution, especially in compact cities like Singapore. For some urban road tunnels, tunnel characteristics such as tunnel configurations, geometries, provisions of tunnel electrical and mechanical systems, traffic volumes, etc. may vary from one section to another. These urban road tunnels that have characterized nonuniform parameters are referred to as nonhomogeneous urban road tunnels. In this study, a novel quantitative risk assessment (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…The QRA models used six events, namely, fire, flooding, chain, collision, tunnel collapse, explosion, and spillage, for risk assessment in the tunnels of urban areas [17,18]. Meng et al in [19] suggested a novel Quantitative Risk Assessment (QRA) model to calculate the risks of non-homogenous urban road tunnels, because the existing QRA models for road tunnels are inapplicable in the road tunnels. This technique uses principle named technical segmentation principle in which the roads of the urban area are divided into many similar sections.…”
Section: Related Workmentioning
confidence: 99%
“…The QRA models used six events, namely, fire, flooding, chain, collision, tunnel collapse, explosion, and spillage, for risk assessment in the tunnels of urban areas [17,18]. Meng et al in [19] suggested a novel Quantitative Risk Assessment (QRA) model to calculate the risks of non-homogenous urban road tunnels, because the existing QRA models for road tunnels are inapplicable in the road tunnels. This technique uses principle named technical segmentation principle in which the roads of the urban area are divided into many similar sections.…”
Section: Related Workmentioning
confidence: 99%
“…Some urban tunnels have complex ''mainline and branches'' configurations, such as slip-roads or on-and off-ramps connecting tunnel traffic to the ground road network (Meng et al, 2011). So ''complex'' here means complex configurations with multiple entry and exit ramps.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the safety evaluation for expressways is of great importance for road authorities. The risks are usually measured by the number of traffic accidents and/or the consequences of those accidents in terms of fatalities and injuries (Meng and Qu 2012b;Meng, Qu, Wang, et al 2011). This is generally regarded as a reactive rather than a proactive approach because road safety could only be assessed after the accidents have occurred (Jin et al 2011;Meng, Qu, Yong, and Wong 2011).…”
Section: Introductionmentioning
confidence: 99%